Optimization techniques for variable selection in binary logistic regression model applied to desire for children data. - Sarkar, S.K.; Midi, Habshah (Science Publications, 2009)
Problem statement: The population problem is the biggest problem in the world. In the global and regional context, Bangladesh population has drawn considerable attention of the social scientists, policy makers and international organizations. Bangladesh is now worlds 10th populous country having about 140 million people. The recent experience of Bangladesh shows that fertility can sustain impressive declines even when womens lives remain severely constrained. Recent statistics also suggest that, despite a continuing increase in contraceptive prevalence rate (56%), the expected fertility decline in Bangladesh has stalled.